2020
DOI: 10.29252/mlj.14.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Beetroot Juice Consumption on the Lipid Profile of Female Soccer Players

Abstract: Background and Objective: It is desirable for athletes, especially female soccer players, to consume beetroot beverage during training as a way of improving both health and performance ,. Therefore, the objective of this study was to assess the effect of beetroot juice intake on lipid profile in female soccer players. Methods: Young and well-trained female soccer players (N=20) were included in a randomized placebo-controlled crossover study. They were categorized into two groups: experimental (beetroot bevera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The hypolipidemic effect of beetroot juice or extract is well-reported in healthy individuals, rodents, rabbits fed a “cholesterol diet”, and diabetic animals [ 51 , 52 , 69 , 70 , 71 , 72 ]. In most of these studies, the beneficial effects of beer root included lowering circulatory CHOL, TGs, and LDL-c levels and increasing HDL-c levels.…”
Section: Discussionmentioning
confidence: 99%
“…The hypolipidemic effect of beetroot juice or extract is well-reported in healthy individuals, rodents, rabbits fed a “cholesterol diet”, and diabetic animals [ 51 , 52 , 69 , 70 , 71 , 72 ]. In most of these studies, the beneficial effects of beer root included lowering circulatory CHOL, TGs, and LDL-c levels and increasing HDL-c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors reported that the hypoglycemia induced by BE is mediated by several interconnected mechanisms such as decreasing intestinal absorption, promoting the generation of pancreatic beta cells, improving insulin clearance via increasing the expression of glucose receptors, suppressing hepatic gluconeogenesis-related enzyme, and enhancing insulin peripheral sensitivity. In addition, the hypolipidemic effect of BE was reported in diabetic animal models of type 1 and 2, as well as in rodents fed high-calorie diets [ 5 , 30 , 31 , 32 , 33 ]. Previously, we have shown that feeding BE can reverse insulin resistance and the release of free fatty acids from adipose tissue [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the polyphenols (e.g., betalains) and nitrate found in the beetroot may have contributed to the decrease in insulin concentration. In addition to the properties of beetroot that are beneficial for glycemic control, two studies [ 57 , 58 ] have highlighted its effect on lipid profile variables (i.e., TC, LDL-c, HDL-c, and TG), demonstrating reduced concentrations of TC, LDL-c, and TG after a single dose [ 58 ] and six weeks [ 57 ] of beetroot juice supplementation. The mechanism by which beetroot can lead to changes in lipid metabolism is not entirely understood.…”
Section: Discussionmentioning
confidence: 99%